Safety of Creatine Supplementation in Active Adolescents and Youth: A Brief Review - Jagim, Andrew R.; Stecker, Richard A.; Harty, Patrick S.; Erickson, Jacob L.; Kerksick, Chad M. (Frontiers in Nutrition, 2018)
Creatine has been extensively researched and is well supported as one of the most effective dietary supplements available. There is overwhelming support within the literature regarding the ability of creatine to augment performance following short term (5-7 days) and long-duration supplementation periods. There is also strong support for creatine regarding its safety profile and minimal risk for adverse events or any negative influence on markers of clinical health and safety. Recent research has also highlighted the ability of creatine to confer several health-related benefits in select clinical populations in addition to offering cognitive benefits. Creatine is also a popular supplement of choice for adolescent athletes; however, research in this area is extremely limited, particularly when examining the safety and efficacy of creatine supplementation in this population. Therefore, the purpose of this review was to highlight the limited number of studies available in adolescent populations and systematically discuss the topic of safety of creatine supplementation in a younger population.